2009
DOI: 10.1039/b905870b
|View full text |Cite
|
Sign up to set email alerts
|

Highly crystalline niobium oxide converted from flux-grown K4Nb6O17 crystals

Abstract: Highly crystalline niobium oxide (Nb 2 O 5 ) nanotubes without defects such as bent and node were successfully prepared by a two-step process. The first step entails making high quality, layered K 4 Nb 6 O 17 crystals as a precursor material. In this study, well-developed, highly crystalline, layered K 4 Nb 6 O 17 crystals were readily grown by the rapid cooling of a KCl flux at a holding temperature of 800 C and a cooling rate of 300 C h À1 . The grown layered crystals of K 4 Nb 6 O 17 were transparentcolorle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The K 4 Nb 6 O 17 crystals were found to have welldeveloped plate-like forms and relatively uniform size compared with those prepared by a solid-state reaction. In a previous study, the crystal phases were identified as K 4 Nb 6 O 17 based on the XRD pattern, and the diffraction intensity of the (0 4 0) plane was predominant [13]. These highly crystalline K 4 Nb 6 O 17 layers were exfoliated into individual nanosheets via the proton-exchange and exfoliation processes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The K 4 Nb 6 O 17 crystals were found to have welldeveloped plate-like forms and relatively uniform size compared with those prepared by a solid-state reaction. In a previous study, the crystal phases were identified as K 4 Nb 6 O 17 based on the XRD pattern, and the diffraction intensity of the (0 4 0) plane was predominant [13]. These highly crystalline K 4 Nb 6 O 17 layers were exfoliated into individual nanosheets via the proton-exchange and exfoliation processes.…”
Section: Resultsmentioning
confidence: 99%
“…First, high-quality, layered K 4 Nb 6 O 17 crystals were grown by the cooling of a KCl flux. Detailed crystal growth procedures have been reported previously [13]. Next, NbO x nanosheets were prepared by exfoliation of the fluxgrown K 4 Nb 6 O 17 crystals.…”
Section: Preparation Of the Nbo X Nanosheet Suspensionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7]9] Recently, various 1D metal oxide compounds (such as tungstates, molybdates, niobates, tantalates, and titanates) were synthesized to be high potential photocatalysts. [2][3][4][5][6]9,[11][12][13] Among them, sodium hexatitanate (Na 2 Ti 6 O 13 ) crystal has been studied as a photocatalyst for the degradation of toxic substances and the decomposition of pure water and as oxygen electrodes in potentiometric sensors for O 2 and CO 2 . [14,15] In addition, Na 2 Ti 6 O 13 forms the whisker structure, which is a needle-shaped single crystal with near theoretical strength due to its perfect geometry.…”
Section: Introductionmentioning
confidence: 99%